Protective effects of Scoparia dulcis L. extract on high glucose-induced injury in human retinal pigment epithelial cells - Lin, Heng-Dao; Lee, Yuan-Chieh; Chiang, Chien-Yi; Lin, Yu-Jung; Shih, Cheng Yen; Tsai, Rong-Kung; Lin, Pi-Yu; Lin, Shinn-Zong; Ho, Tsung-Jung; Huang, Chih-Yang (Frontiers in Nutrition, 2023)
Diabetic retinopathy (DR) is a major cause of vision loss in diabetic patients. Hyper-glycemia-induced oxidative stress and the accumulation of inflammatory factors resulting in blood-retinal barrier dysfunction and pathogenesis of DR. Scoparia dulcis L. ex-tract (SDE), a Traditional Chinese medicine, has been recently recognized for various pharmacological effects, including anti-diabetic, anti-hyperlipidemia, anti-inflammatory, and anti-oxidative activities. However, there is no relevant research on the protective effect of SDE in DR. In this study, we treated high glucose (50 mM) in human retinal epithelial cells (ARPE-19) with different concentrations of SDE and analyzed cell viability, apoptosis and ROS production. Moreover, we also analyzed the expression of Akt, Nrf2, catalase and HO-1 showed that SDE dose-dependently reduced ROS production and attenuated ARPE-19 cell apoptosis in a high glucose environment. Briefly, we demonstrated that SDE exhibited anti-oxidative and anti-inflammatory ability in protecting retinal cells from high glucose (HG) treatment. Moreover, we also investigated the involvement of the Akt/Nrf2/HO-1 pathway in SDE-mediated protective effects. These results suggest SDE as a nutritional supplement that could benefit patients with DR.